2006
DOI: 10.1177/0091270006289851
|View full text |Cite
|
Sign up to set email alerts
|

High‐Dose Statin Treatment Does Not Alter Plasma Marker for Brain Cholesterol Metabolism in Patients With Moderately Elevated Plasma Cholesterol Levels

Abstract: Statins inhibit endogenous cholesterol synthesis, up-regulate low-density lipoprotein (LDL) receptor expression in mammalian liver cells, and thus decrease circulating LDL-cholesterol concentrations. As cholesterol seems to play a role in the development of neurodegenerative diseases, it is of interest to evaluate the effect of high dosages of statins (eg, atorvastatin or simvastatin) on brain cholesterol metabolism. Plasma samples from 44 participants (aged 30-69 years, 16 men and 18 women) of an earlier rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…However, animal studies indicate that administration of high doses of simvastatin or pravastatin does not change total brain cholesterol levels 52,53 Furthermore, a study of human volunteers showed that administration of a highdose of either simvastatin or pravastatin did not change plasma 24(S)-hydroxycholesterol to cholesterol ratio, a surrogate marker of brain cholesterol homeostasis. 54 In addition, moderate or heavy past or present alcohol use was reported in a significant proportion of the psychiatric patients. In this group of patients, we found a significant deficit in cholesterol levels in white matter but not in grey matter relative to patients reported to have no or only social alcohol use.…”
Section: Limitationsmentioning
confidence: 99%
“…However, animal studies indicate that administration of high doses of simvastatin or pravastatin does not change total brain cholesterol levels 52,53 Furthermore, a study of human volunteers showed that administration of a highdose of either simvastatin or pravastatin did not change plasma 24(S)-hydroxycholesterol to cholesterol ratio, a surrogate marker of brain cholesterol homeostasis. 54 In addition, moderate or heavy past or present alcohol use was reported in a significant proportion of the psychiatric patients. In this group of patients, we found a significant deficit in cholesterol levels in white matter but not in grey matter relative to patients reported to have no or only social alcohol use.…”
Section: Limitationsmentioning
confidence: 99%
“…Sitosterol and campesterol concentrations were analyzed using gas chromatography-flame ion detection (GC-FID) as described previously [12] and concentrations are expressed as mg/dL. 7b-Hydroxy(OH)-campesterol, 7b-OH-sitosterol, 7-keto-campesterol and 7-keto-sitosterol were analyzed by gas chromatography-mass spectrometry (GC-MS-MS) according to the procedure as described by Husche et al [13] with minor modifications related to the use of a GC-MS triplequad instead of a GC-MS singlequad and are expressed as ng/mL.…”
Section: Blood Sampling and Analysesmentioning
confidence: 99%
“…Because its measurement is easier in humans, the authors of nine different clinical studies have measured 24S-hydroxycholesterol, and majority of them demonstrated its reduction both in plasma and in CSF. [16][17][18][19][20][21][22][23] There were just two exceptions. In a study in which the authors used hydrophilic pravastatin, concentrations of 24S-hydroxycholesterol in plasma were decreased only nonsignificantly.…”
Section: Effect Of Statins On Cholesterol Synthesis In Brainmentioning
confidence: 99%
“…Only three recent clinical studies have measured 27-hydroxycholesterol in plasma 21,22,24 and one also in CSF. 23 In all of them 21,22,24 the authors found a significant reduction in plasma level of 27-OH-cholesterol after statin treatment, whereas the CSF levels were nonsignificantly reduced (in the study by Hoglund et al 24 ).…”
Section: Effect Of Statins On 27-hydroxycholesterolmentioning
confidence: 99%